Comportamento de genótipos de feijoeiro sob cultivo orgânico - Altoé, Marcus (2007)
The common bean plant (Phaseolus vulgaris L.) is one of the spread crops in Brazil due to its economical character and high social meaning, since it is the population´s basic food. The consumers and producers concern with the personal health and environme